(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Under the guidance of the “dual carbon” goal, the country has entered a new development period of low carbon and green, and brand building and value enhancement have become an important direction of the current market development. As a highly polluting apparel industry, the various apparel brands under its industry must also seize the opportunity for development and low-carbon transformation and become an important force in promoting carbon peak and carbon neutrality. This can be done by enhancing the low-carbon image of the brand, actively exploring the mode and experience of sustainable production and consumption, and vigorously promoting the green transformation of the global fashion industry. In this paper, we first sorted out. We summarised the related research on low-carbon brand value. We explored the problems of apparel brands failing to practice low-carbon development from three basic dimensions: product, brand marketing and internal brand management. We then proposed corresponding solutions and strategies to enhance brand value. The study finds that apparel brands can try to increase innovation investment to create product and service differentiation, improve the internal management mode to enhance the competitiveness of the low-carbon market, and actively fulfil the brand’s social responsibility to contribute to the realisation of the national goal of “dual carbon”.